(untitled) (The International Journal for Scientific Research, 2026)
The study aimed to identify the degree to which school administrations practice transcendent leadership and its relationship to institutional excellence in public schools in the Sultanate of Oman from the teachers’ perspective. To achieve the objectives of the study, a descriptive correlational approach was employed. The questionnaire was adopted as the primary instrument for collecting data and information, and its validity and reliability were verified. It was administered to a sample of (362) male and female teachers in public schools in Al Dhahirah and Al Buraimi Governorates in the Sultanate of Oman. The results indicated that the overall level of school administrations’ practice of transcendent leadership in public schools was moderate. They also revealed that the overall level of institutional excellence in public schools, from the teachers’ perspective, was moderate. Furthermore, the findings showed a statistically significant positive correlation between all dimensions of the transcendent leadership practice scale and the dimensions of the institutional excellence scale in public schools in the Sultanate of Oman. However, the relationship between the two variables was not very strong. The study recommended the need to develop training programs for school administrations to enhance transparency in discussions and dialogues within schools, conduct periodic studies to identify teachers’ professional needs and work toward meeting them, effectively implement a “Respect for All” policy, and improve the work environment to make it comfortable and suitable.